GESTÃO POR COMPETÊNCIAS: ESTUDO DE CASOS SOBRE A IMPLANTAÇÃO DO PROGRAMA EM DUAS EMPRESAS QUE OPERAM NO BRASIL - ASSIS , MÁRCIO SOUSA (2016)
This dissertation research aimed to verify how and why companies apply studied management by competence, the type of perfomance assessment, the main contributions, the facilities and difficulties of the program. They were considered for the survey two companies reported using the management skills as a management method. We used the qualitative research method. We opted for the case study, transversal method where all measurements were made in a single moment. It is a comprehensive study that seeks to understand the facts after they have occured. The unit of analysis was the management processes for skills, performance policy evaluation and analysis of the responses of respondents. The findings of the reserach revealed that organizations seek to integrate studied the organizational strategies with competency management program, the programs are similar, and most important factor: they have the support of the compan´s board. The same conduct annual performance review and give feedback to employees. The focus of the programas is the development of people and the development of skills to meet the goals. However, they have adjustments to be made, as in the study of one of the companies in which the program is not intended for the vast majority of employees. It is a great challenge for the company, as if the situation is not reviewed, may cause harmful effects, such as lack of motivation, dissatisfaction, reduced productivity, workers have no focus no professional growht view. In this way there are not likely to contribute to the achievement of the organization´s strategies. Another issue to be examined is whether the type of performane measurement used by the two organizations, where only the manager evaluates the employee, is the ideal type. In the literatyre, the authors advocate the performance evaluation that 360 degrees is the most complete type and it can bring more benefits. As contributions to the organizations were cited improvement in communication, clarity to know what to evaluate and how to evaluate and easier to resolve questions related to the succession plan.